Investigation of photocurrent generation in dye sensitised solar cells based on nanostructured ZnO electrodes. (2nd January 2016) - Hosseinnezhad, M.
Abstract : A series of metal free organic dyes based on indoline were used as photosensitiser in ZnO dye sensitised solar cells. The results show that the organic dyes containing phenothiazine as the donor group and cyanoacrylic acid as the acceptor group gave the maximum conversion efficiency of 3·22%. In this study, the influence of cheno as antiaggregation agent has been investigated. The results illustrate that the conversion efficiencies are improved in the presence of antiaggregation agent due to reduced aggregation. Conversion efficiency dye 4 is 3·82% in the presence of cheno as antiaggregation agent. Ultraviolet–visible spectrophotometry of the metal free organic dyes in solution and on a ZnO substrate were carried out in order to assess changes in the status of the dyes. The results show that the dyes from J type aggregate on the ZnO substrate.